Padrão espacial de plantas lenhosas em uma Floresta Tropical Sazonalmente Seca: o papel das características funcionais nas associações espaciais intra e interespecíficas - Souza, Luiz Tiago Soares de (2023)
Spatial point-pattern analysis in plants has been widely used and is a powerful tool for detecting biological interactions and process. The investigation of these interactions together with the functional traits of woody plants can help to understand the processes that generate these patterns, whether linked to dispersal limitation, environmental filtering, niche aspects,competition, facilitation and coexistence. Here, we investigate the relationships between thespatial patterns of woody plant species in a Seasonally Dry Tropical Forest (SDTF) and their characteristics or functional traits to understand the processes generating the patterns andstructure woody populations and communities. We propose to answer the following questions:i) which spatial patterns are predominant in Seasonally Dry Tropical Forests (SDTFs):interspecific associations, indicating facilitating structuring processes, or intraspecific spatialassociations, indicating competitive structuring processes? ii) acquisitive functional traits andlinked to dispersal limitation can explain the intraspecific spatial patterns of woody species inSDTFs? iii) interspecific spatial patterns are related to key functional traits in resourceacquisition and conservation? Our results indicate that intraspecific aggregated spatial patternsare predominant at both population and community levels, contrary to what was expected in acontext of abiotic stress. We adjusted linear models relating intraspecific aggregation tofunctional traits of resource acquisition and traits linked to dispersal limitation, which wereextremely effective in explaining the variation in intensity and type of pattern at variousneighborhood spatial scales (R² = 0.90 to 0. 98), with wood density, dispersal syndrome andseed mass being the most important characteristics for intraspecific aggregation. Interspecificspatial patterns indicate that competition is more important than facilitation in SDTFs, at aneighborhood scale of 0 to 15 m. There was low correlation between patterns of interspecificspatial association, and non-significant, on a scale of 1 to 15m. Intraspecific spatial associations,mediated by dispersal limitation, environmental filtering, functional traits and bilateral intraspecific competition structure relationships between plants and allow coexistence betweenspecies not only in tropical rainforests and other non-tropical forest formations, but also in SDTFs, reducing encounters with heterospecific individuals, competitive exclusion andpromoting diversity.